2006
DOI: 10.1002/hyp.6203
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal, spatially distributed modelling of accumulation and melting of snow for computing runoff in a long‐term, large‐basin water balance model

Abstract: Abstract:In mountainous regions of mid latitudes, the accumulation and melting of snow plays an important role for the seasonal water balance. These processes not only exhibit a strong seasonality, but also a high spatial variability, which has to be accounted for when establishing distributed water balances in alpine environments. A methodology was developed for seasonal, spatially distributed modelling of accumulation and melting of snow and was embedded in a water balance model that uses only monthly values… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0
10

Year Published

2008
2008
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 21 publications
0
27
0
10
Order By: Relevance
“…However, redistribution of snow requires only two additional parameters but allows for more realistic boundaries (see Kling et al, 2006) of the snowmelt factors (see Supplement of this article). However, more work needs to be carried out to account for that issue.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, redistribution of snow requires only two additional parameters but allows for more realistic boundaries (see Kling et al, 2006) of the snowmelt factors (see Supplement of this article). However, more work needs to be carried out to account for that issue.…”
Section: Discussionmentioning
confidence: 99%
“…12). Yet, accounting for snow redistribution allows the modeller to use D U values within or close to the range proposed by Kling et al (2006), while the standard version of the model leads to the best results if higher and therefore unrealistic D U values are used (see the Supplement of this article).…”
Section: Parameter Equifinalitymentioning
confidence: 99%
“…Similarly, most regions seem to require more sophisticated representations of the snow accumulation and melt process. It seems quite reasonable to suggest that some representation of the submonthly temporal and/or subcatchment spatial distributions of hydrological fluxes may actually prove to be critical [e.g., Kling et al, 2006], or perhaps some process-based formulation that approximates the terms of the energy balance using daily data [Walter et al, 2005]. And while, in some cases, it may be possible to parameterize these subscale processes to enable continued modeling at the monthly catchment scale, in other cases such an approach may fail with the only recourse being to model at some finer spa-tiotemporal scale.…”
Section: Discussionmentioning
confidence: 99%
“…The study by Singh et al (2006) in the Himalayan basin reported an 87% glacier melt contribution to the total runoff. Kling et al (2006) carried out a study for the whole of Austria and found the runoff coefficient for snowmelt in the alpine parts to be greater than 80%, and for the lowlands less than 50%.…”
Section: Introductionmentioning
confidence: 99%